Islamic Banking Theory and Practice: A Survey and Bibliography of the 1995-2005 Literature - Tahir, Sayyid (SESRIC, 2007)
This paper highlights salient features of the Islamic banking literature during 1995-2005 (section 1). It reports on major developments on the Islamic banking scene in selected Muslim and other countries (section 2). It briefly looks at performance of the banks on the Shari'ah benchmark (section 3). Last but not least, it identifies the direction for future research (section 4). The paper also gives a classified bibliography of the Islamic banking and finance literature produced during 1995-2005.